Implementing augmented reality to improve students’ biology learning outcomes: Gender-based effect - Badrud Tamam; Aloysius Duran Corebima (International Journal of Evaluation and Research in Education (IJERE), 2023)
The current study examined the difference in students’ biology learning outcomes based on gender following the implementation of Augmented reality (AR). A gender equality study is useful as a foundation for establishing gender-sensitive learning. Gender equality promotes higher productivity and development outcomes, therefore it has favorable effects on economic and technological growth, as well as social fairness. We administered a quasi-experimental non-equivalent pretest-posttest control group design. The research population is all of class X public high school in Pamekasan Regency, Indonesia. The research samples were 56 senior high school students in class X. The classes that will be used as research samples are first tested for equality. The equivalence test analysis will use analysis of variance (ANOVA) by utilizing the SPSS 23.00 for windows program. Participants’ learning outcomes were measured using an essay test. The revised Blooms taxonomy indicators were used as the reference to construct the tests. The test covered the indicators of applying (C3), analyzing (C4), and synthesizing (C5). The participants’ answered were evaluated using a 4-point scale rubric adopted from Hart. One-way ANCOVA (analysis of covariance) was performed, involving the pretest scores as the covariate. The results showed that there was no difference in biology learning outcomes between male and female students involved in this study (p>0.05). These findings demonstrate that the implementation of augmented reality can close the gender gap in biology education. Augmented reality can be a solution to improve the learning environment in biology classrooms and facilitate gender-based learning demands.